KEMAMPUAN BERPIKIR KRITIS DALAM PEMAHAMAN TEKS EKSPLANASI PADA SISWA KELAS V SEKOLAH DASAR - Nurmalasari, Wahyu (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
Learning activities cannot be separated from the thinking process. Critical thinking is an activity in assessing and finding errors, while creative thinking is an activity related to creating related to intelligence and imagination. Through interviews with teachers, it shows that students' ability to think critically is relatively low with students not being able to write appropriate ideas or statements according to events or topics assigned by the teacher. When writing explanatory texts, students still experience confusion in distinguishing between other texts. Teachers also have not used supporting media to develop students' critical thinking skills, such as pictures or videos of events that will be written into explanatory texts. This research aims to describe students' critical thinking abilities in understanding explanatory text with image stimuli. The type of research is qualitative descriptive research. The limitations of this research lie in the material, namely explanatory text. The research subjects were 19 class V students at SDN Madyopuro 6 Malang. Data collection using essay test questions. Data analysis by reducing, explaining the data, and drawing conclusions and checking the validity of the data. The results of this research analysis show that critical thinking skills in understanding explanatory text found several answer patterns. Student answer patterns are related to the ability to interpret, analyze and assess in the form of explicit patterns and statements. This is because most students only write written answers in the picture and only write statements without reason. Based on these patterns, the majority of students' abilities are still classified as low criteria.